LAW ENFORCEMENT ON ILLEGAL CIGARETTE DISTRIBUTION BY CUSTOMS INVESTIGATORS IN EAST JAVA I REGION - Ardiansah, Wisnu; Sugiharto, Sugiharto; Suroso, Imam (jfpublisher, 2025)
The circulation of illegal cigarettes is a serious challenge for the state in maintaining economic stability and public welfare. Many small cigarette entrepreneurs in Indonesia are concerned about the widespread distribution of illegal cigarettes. They are dissatisfied with the performance of Customs officers, who are perceived as not being stringent enough in enforcing regulations. The impact of the extensive circulation of illegal cigarettes, particularly those without excise stamps, causes legal cigarette entrepreneurs to face difficulties in competing, resulting in a decline in their production. Although many legal cigarette entrepreneurs have paid excise to the state, the reality is that the circulation of illegal cigarettes in the market is increasing, leading to a decrease in state revenue. Illegal cigarettes, sold at lower prices, tempt consumers to choose illegal products over legal and registered ones. This situation is very detrimental and highlights the need for firm and consistent actions from Customs officers. The Civil Servant Investigators (PPNS) of Customs and Excise play a crucial role in uncovering and taking action against such circulation within their jurisdiction. This study analyzes the efforts of the PPNS of Customs and Excise in uncovering illegal cigarettes at the Regional Office of the Directorate General of Customs and Excise of East Java I through a juridical-empirical approach. The research methodology involves document study, interviews, and direct observation. The results show measures such as increased supervision, socialization, inter-agency cooperation, and enforcement. Constraints include a lack of information regarding perpetrators and online circulation patterns. It is recommended that the PPNS enhance coordination, tracking systems, and regulations, as well as increase public awareness about the dangers of illegal cigarettes. These measures are expected to improve the effectiveness in handling the circulation of illegal cigarettes.